2017
DOI: 10.1039/c7ta04615d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the physical origin behind disorder, heterogeneity, and reconstruction and their correlation with the photoluminescence lifetime in hybrid perovskite thin films

Abstract: Organolead halide perovskites are interesting light-absorbing materials for solar cells and light-emitting devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The higher responses correspond to some grains although the overall responses are lower than illumination condition. This can be originated from different activation energy of iodide and bromide and their migration in grains with different sizes in the film, resulting from heterogeneously compositional difference, chemical segregation, and defect states due to solution processing. …”
Section: Resultsmentioning
confidence: 99%
“…The higher responses correspond to some grains although the overall responses are lower than illumination condition. This can be originated from different activation energy of iodide and bromide and their migration in grains with different sizes in the film, resulting from heterogeneously compositional difference, chemical segregation, and defect states due to solution processing. …”
Section: Resultsmentioning
confidence: 99%
“…2(d The observed increased PL yield and faster recombination rate can be explained in terms of a certain structural and chemical modifications of the MAPbI 3 film remained after laser patterning. Pre vious studies on strong laser irradiation of MAPbI 3 concluded that its surface layer always contained excess of PbI 2 [8,9]. Such modification is highly possible considering that sublimation of methyl ammonium proceeds at temperature above 160 o that can be easily reached within the laserirradiated section of the MAPbI 3 film.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike their encouraging efficiency, lead and tin based perovskite solar cells faced from both the toxicity of Pb metal and device instability [73][74][75], which limit the practical applications. Consequently, a great deal has been dedicated to the look for alternative perovskite materials such as lead and tin free halide double perovskites and lead and tin free all inorganic perovskites [76][77][78][79][80][81].…”
Section: Challenges In Lead and Tin Free All-inorganic Halide Double ...mentioning
confidence: 99%